Financial Reform and the restructuring of Spanish banks and savings banks sector. (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
This article frames the Spanish economic crisis in the context of the international financial crisis, explains its impact on the Spanish financial sector, the measures taken to restructure the sector and finally reflects upon the sector’s positioning forthe near future.
Keywords: economic crisis; international financial crisis; real estate sector; banks; savings banks; European Central Bank; FROB; SIP; SAREB.